Commit* to change? A call to end the publication of the phrase ‘commit* suicide’ - Nielsen, Emma; Padmanathan, Prianka; Knipe, Duleeka (F1000Research, 2016)
Background: Countering stigma is a fundamental facet of suicide prevention efforts. Integral to this is the promotion of accurate and sensitive language. The phrase ‘commit* suicide’ has prompted marked opposition primarily due to the connotations of immorality and illegality. Methods: The study investigated the frequency of the use of the wordstem ‘commit’, in relation to self-harm and suicidal behaviours, in the three leading suicide-specific academic journals between 2000 and 2015. Results: One third (34%) of articles published since the year 2000 used the word ‘commit*’ when describing an act of self-harm or suicide. Over half of these articles (57%) used the phrase on more than one occasion, with 6% using it more than 10 times in the same manuscript. The percentage of papers utilising the word ‘commit*’ has fluctuated over time, but there is a promising downward trend in the use of this phrase from 33% in 2000 to 13% in 2015 (p < 0.001). Discussion: We advocate for the implementation of publication requirements regarding the language used when discussing suicide. Whilst we call for collective responsibility amongst academics and clinicians, editors hold a unique position in ensuring that outdated, inaccurate and stigma-laden terms are expunged from the scientific literature.